Nature of Human Rights - López Dawson, Carlos (2016)
In the formation of a new Constitution the constituents will require to know or reach an agreement on the nature of human rights; then, to determine how the State will enforce the respect to those rights. To do so, it is necessary to resort to the history and evolution of these rights, and the present work aims to contribute to an efficient productive debate about the nature of human rights, so that citizens can decide on the understanding that this is a thoughtful democratic and humanistic founded decision. The analysis is in the actual technical-ideological republican system which correspond to the current state of international law